Mechanisms of self-screening in pure ice - Chikina, I.; Shikin, V. (Физика низких температур, 2015)
Possible approaches to a correct account of the Coulomb interaction in system of proton-hydroxyl pairs in
pure ice (a proton version of intrinsic semiconductor) are discussed for a possibility to evaluate correlation properties
of semiconducting media.